ARGON PLASMA COAGULATION IN THE TREATMENT OF BARRETT’S ESOPHAGUS IN COMBINATION WITH HIATAL HERNIA - Babii, O.M.; Prolom, N.V.; Shevchenko, B.F.; Tarabarov, S.O.; Poliak, N.V.; Mylostуva D.F.; Dementii, N.P. (World of Medicine and Biology, 2023)
141 patients were examined in the Department of Digestive Surgery of the SI “Institute of gastroenterology of NAMS of Ukraine” in 2017–2022 to improve the treatment tactics of Barrett’s esophagus with hernias of the esophageal opening of the diaphragm. All patients were diagnosed with hiatal hernia by X-ray examination. The diagnosis of Barrett’s esophagus was confirmed by an endoscopic examination with an NBI mode and high-resolution (HD) device, with a visual assessment of the condition of the esophageal mucosa and the sampling of biopsies for histological examination. In 5 (3.2 %) cases, cylindrical cell metaplasia of the esophagus was diagnosed with signs of intestinal metaplasia and mild dysplasia. A two-stage treatment method was chosen: the first one – argon plasma coagulation of the esophageal mucosa, and the second – elimination of hiatal hernia during elective antireflux surgery.